\(\displaystyle{\left({3}{t}-{2}\right)}{\left({7}{t}-{4}\right)}\)

By using FOIL method, The order of multiplying is First terms, Outside terms, Inside terms and Last terms of the given two polynomials.

That is,

\(\displaystyle{3}{t}{\left({7}{t}\right)}={21}{t}^{{2}}\)

\(\displaystyle{3}{t}{\left(-{4}\right)}=-{12}{t}\)

\(\displaystyle-{2}{\left({7}{t}\right)}=-{14}{t}\)

\(\displaystyle-{2}{\left(-{4}\right)}={8}\)

Now by combining all the result we get

\(\displaystyle{\left({3}{t}-{2}\right)}{\left({7}{t}-{4}\right)}={21}{t}^{{2}}-{12}{t}-{14}{t}+{8}\)

\(\displaystyle={21}{t}^{{2}}-{26}{t}+{8}\)

By using FOIL method, The order of multiplying is First terms, Outside terms, Inside terms and Last terms of the given two polynomials.

That is,

\(\displaystyle{3}{t}{\left({7}{t}\right)}={21}{t}^{{2}}\)

\(\displaystyle{3}{t}{\left(-{4}\right)}=-{12}{t}\)

\(\displaystyle-{2}{\left({7}{t}\right)}=-{14}{t}\)

\(\displaystyle-{2}{\left(-{4}\right)}={8}\)

Now by combining all the result we get

\(\displaystyle{\left({3}{t}-{2}\right)}{\left({7}{t}-{4}\right)}={21}{t}^{{2}}-{12}{t}-{14}{t}+{8}\)

\(\displaystyle={21}{t}^{{2}}-{26}{t}+{8}\)